Sports business management decision making around the globe - Foster, George 1948-; O'Reilly, Norm, 1973-; Davila, Antonio (Routledge, Taylor & Francis, 2016)
Sports Business Management will equip students with a comprehensive understanding of the sport industry. With a focus on management, strategy, marketing, and finance, the decision-making approach of the book emphasizes key concepts while translating them into practice. Foster, O'Reilly, and Davila present a set of modular chapters supported with plenty of examples, mini-cases, and exercises to help students apply the decision-making approach to real-world situations. Covering an international array of sports and organizations - including the Olympic Games, FIFA World Cup, US Major League Baseball, and more - the book also covers unique topics such as diversity in sport, the impact of technology, and social media. Rounding this out, the book provides around 50 Harvard / Stanford cases, along with case notes for instructors.